하천(河川)을 고려한 호소(湖沼)의 물 순환 정책방안 -충남·대전지역 농업용 호소의 체류시간을 중심으로 - 이상진; Yi, Sang-Jin (한국콘텐츠학회 논문지, 11(9), 2011)
Several problems occurred due to the use of the wrong water cycle system in the watershed. This was caused by a dry stream in the lower parts of the tributaries and the deterioration in value of usage by water pollution in accordance with water storage. This was maintained for a long period of time in the reservoir which secured the agricultural water. As a result of the operational status in the agricultural reservoirs focused on Chungcheongnam-do and Daejeon metropolitan city, a dry stream appeared because hydraulic retention time(HRT) in the majority of reservoirs was maintained for 8 months of the year. The water quality in the agricultural reservoir was fairly related to the water cycle system due to rainfall and input of pollutants from the population and livestock in the watershed. Consequently, the storage water volume and the time period of the water in the reservoir should be controlled by the reduction of the pollution load in the water and the prevention of a dry stream. Also, the water cycle system in the watershed should be improved by maintaining a short HRT of the reservoir. 농업용수를 확보하기 위하여 조성한 호소에 장기간 물을 담수함에 따라 수질오염으로 이용가치 저하와 하류 하천이 건천화 되어 하천의 기능을 상실하는 등 유역내 잘못된 물 관리체계로 여러 가지 문제점이 발생하고 있다. 충남 대전지역을 중심으로 농업용 호소의 운영현황을 조사한 결과 대부분 호소수의 체류시간은 8개월 이상을 유지하여 그 기간 동안 하류하천의 건천화가 나타났고, 호소수의 수질은 생활계 및 축산계 오염물질의 유입과 강수량에 따른 물 순환특성과 상당히 밀접한 것으로 분석되었다. 따라서 호소 유역내수질오염물질 저감과 함께 하류하천이 건천화가 되지 않도록 담수량과 담수시기를 조절하고, 호소수 체류 시간은 가급적 짧게 유지하는 등 유역내 물 순환체계를 개선할 필요가 있다.